PERCEPTION OF TOURISTS TOWARD COMMUNITY-BASED FESTIVAL OF KUTA MAJELANGU MARKET - Made Ruki; Ni Gst Nym Suci Murni; Ida Ayu Elistyawati (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
The aim of this research was to identify foreign tourist perception toward service of KutaMajelangu Market as an Attraction of community-based tourism. Foreign tourist’s perception was analyzed by Likert scale. This research used various approaches such as: social and culture, community based tourism, sustainable tourism, and perception theory. Respondents were taken from foreign tourist come from many countries such as Japan, Australia, China, America, Germany, Austria, Holland, and British, while the informants were taken from districts officers, around Kuta Village: such as the head of traditional village known as bendesa, head od subvillage/kelihan banjar, and Kuta community leaders. Data were taken from observation, Interview, questionnaire, and some documents. The results of this study revealed that perception of tourists toward the festival Market Majelangu Kuta as community-based tourist attraction for a variety of requirements had been fulfillment where starting from the land use, planning, management, preservation, benefit economically performed independently by local community. While the perception of tourists toward the activities and services of the Market Majelangu Kuta were well perceived by 79% percent of tourists